Changes in soil chemical properties as affected by application of wastewater spiked with heavy metals - A I HALLI; R SINGH; D GOLUI; D S GURJAR; MAN SINGH; K LAL; R S BANA; SUDHIR KUMAR (The Indian Journal of Agricultural Sciences, 2022)
Wastewater was spiked with cadmium (Cd), chromium (Cr), nickel (Ni) and lead (Pb) at various concentrations and applied in soil under gladiolus crop at research farm of Water Technology Center, ICAR-IARI, New Delhi during 2017. Changes in soil parameters were determined as per the standard methods. Results indicated that soil properties in-terms of pH, organic carbon, phosphorous, potassium and micronutrients (Cu, Fe, Mn, Zn) was not changed significantly, whereas significantly higher salt (EC 0.41 dS/m), nitrogen (161.50 kg/ha) as well as Ni (0.75 mg/kg), Cr (1.64 mg/kg), Cd (0.17 mg/kg) and Pb (2.75 mg/kg) in T5 treated soils were recorded, where highest concentration of metals, i.e. Cd (0.5 mg/L), Cr (5.0 mg/ L), Ni (10 mg/L), Pb (50 mg/L) were spiked in wastewater. It may be concluded that application of metals spiked wastewater irrigation may alter soil functioning by way of elevated levels of metal in soils under pot experiment.